Strategi Penguatan Kinerja Kelompok Usaha Ternak Sapi Perah - Agustian, Egi; Indah Laela Rahmah, Ulfa; Adam Yuliandri, Lili (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2025)
This research was conducted in Girimulya Village, Banjaran District, Majalengka Regency from June 5 to July 5, 2024. This study aims to analyze the internal and external environmental conditions of the group and analyze the group's strengthening strategy in improving the dairy cattle business in the Mekar Mulya Farmer Group. The research method is a survey, the data collection technique in this study was by observation, interviews and recording of the administrators and members of the group as many as 37 respondents. The results of this study indicate that the results of the identification of the internal and external environment of the group obtained a large internal strength factor, namely partners in milk marketing with a value of 0.416 and the lowest internal weakness was not making processed products from milk raw materials with a value of 0.168. The largest external opportunity factor is assistance from the government with a value of 0.325, while the lowest threat is the existence of similar groups in the area with a value of 0.106. The results of the IFE analysis on the group showed a total score of 2.841 and the results of the EFE analysis showed a total score of 2.099. The IE Matrix of the Mekar Mulya Farmers Group occupies a position in cell V, which means guard and maintain.